Social-emotional development in early life: what happens and how to optimize it - Medise, Bernie Endyarni; Wiguna, Tjhin; Dharma Asih, Ni Ketut Susila (Indonesian Nutrition Association, 2022)
The Physical, metabolic, emotional, cognitive, and social development all begin to develop during early years of childhood.. Social and emotional competencies are increasingly recognized as critical for children's success, in school and in later phases of life into adulthood. According to new research, changes in the gastrointestinal tract's development during the early postnatal period can affect brain development and vice versa., collectively called the gut-brain axis. The gut microbiota has an impact on a variety of mental processes and phenomena, as well as being involved in the pathophysiology of a variety of mental and neurological diseases.. Insights in this area can be targeted through dietary treatments to improve cognitive outcomes in newborns by optimizing the link between the gastrointestinal system and the brain. Further, having a healthy and happy human life could be ensured by acquiring adequate and balance microbiota